The Virtues of the Teacher as an Expression of his Authority - Tijūnėlienė, Ona (Acta Paedagogica Vilnensia, 2002)
The article discusses the virtues of the teacher that are most important in the process of education – pedagogical love and justice, as an expression of teacher’s authority. The conceptions of the most famous educators of independent Lithuania are analysed, the positions of training practices are described.
Keywords: pedagogical love; justice; educational authority; the authority of the resolution; pedagogical interaction; sociability; education